An anthropomorphic carving from Pictish Orkney - Lawrence, David (Proceedings of the Society of Antiquaries of Scotland, 2006)
Article on an example of Pictish anthropological art discovered in Orkney, incised on the surface of a cattle bone artefact that is interpreted as a gaming piece. The find is described and compared with related objects, with conclusions that may hold implications for the origins of hnefatafl and the meaning of some Pictish symbols.